Contraceptive Awareness and Practices in Patients With Rheumatic Diseases Using Disease Modifying Anti-Rheumatic Drugs - Gul, Shahzad; Khan, Muhammad Muddasser; Rasheed, Uzma; Tahir, Saira; Zammurad, Shazia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the contraceptive awareness and practices in patients with rheumatic diseases using disease modifying anti-rheumatic drugs. Study Design: Cross-sectional study. Place and Duration of Study: Outpatient of Rheumatology, Department at Pakistan Institute of Medical Sciences, Islamabad Pakistan, from Jan to Apr 2021. Methodology: Patients with any rheumatic disease and taking teratogenic disease modifying anti-rheumatic drugs were included in the study. Patients were asked about if they were counseled regarding the risk of teratogenicity with the antirheumatic drugs and when to stop the drug before pregnancy. Results: Out of total 150 patients, 87 (58.0%) female patients had Rheumatoid arthritis and 26 (17.3%) had Systemic lupus erythematosus. The majority of female patients (104, 69.3%) were using Methotrexate and 21 (14.0%) females were using Leflunomide. Only 53 (35.3%) females were counseled about drug teratogenicity. Most of the female patients (102, 68.0%) were never counseled about the use of contraception while taking anti-rheumatic drugs. The rate of use of contraceptives was even worse and merely 15 (10.0%) females were using contraceptives. Conclusion: Majority of the patients with rheumatic diseases being treated with teratogenic disease modifying anti-rheumatic drugs, were not using any form of contraception. The rate of contraceptive use and counseling regarding contraceptives was noted to be very low.